Arbitrase Syariah Sebagai Solusi Sengketa Bisnis di Indonesia - Edi Riyanto (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
This article discusses the position of the Board of Arbitration Muamalat Indonesia (BAMUI) in Indonesian positive law and political laws of Indonesia. When a business is experiencing a dispute while the company has no strong legitimacy, it is possible that the dispute can not be resolved. The existence of Muamalat Indonesia Arbitration Board has a legal basis and enables other institutions outside the judiciary to be a referee / judge in the settlement of disputes by the parties, it can be seen from the provisions of law No. 14 1970 article 3, paragraph 1 of Law No. 20 in 1999. This arbitration regulation is a solution step in the economy worldto reduce the accumulated burden of the dispute submitted to the court. The political side of Islamic law which is reflected in Act No. 30 of 1999 on Arbitration is an alternative dispute resolution instrument so that it ease the burden on the courts. The arbitration itself is a solution that also ever happened in the time of Caliph ‘Ali bin AbiTalib. So it can be said that the enactment of this arbitration regulation is a step forward to reduce the accumulated burden of the dispute submitted to the court.